Robot-assisted esophagectomy (RAE) versus conventional minimally invasive esophagectomy (MIE) for resectable esophageal squamous cell carcinoma: protocol for a multicenter prospective randomized controlled trial (RAMIE trial, robot-assisted minimally invasive Esophagectomy) - Yang Yang; Xiaobin Zhang; Bin Li; Zhigang Li; Yifeng Sun; Teng Mao; Rong Hua; Yu Yang; Xufeng Guo; Yi He; Hecheng Li; Hezhong Chen; et al. (BMC Cancer, 2019)
Abstract Background Currently, there are three main surgical approaches for resectable esophageal cancer: open transthoracic esophagectomy (OTE), conventional minimally invasive esophagectomy (MIE) and robot-assisted esophagectomy (RAE). Previous studies had demonstrated the better short-term outcomes in MIE or RAE when compared to OTE, respectively. However, to date, no prospective study was designed to compare these two minimally invasive approaches (MIE and RAE). The primary objective of this study is to compare the outcomes on survival, safety and efficacy, quality of life between RAE and MIE in the treatment for resectable esophageal squamous cell carcinoma (ESCC). Methods This study is designed as a multicenter, prospective, randomized, non-inferiority phase III clinical trial, investigating the safety and efficacy of RAE compared with MIE in the treatment of resectable ESCC. Eligible patients are randomly assigned to either RAE (n = 180) or MIE (n = 180) group. The follow-up visits will be scheduled at 3, 6, 9, and 12 months in the first two years, and then every 6 months until the end of the study. During the follow-up period, clinical data and quality of life questionnaires will be examined. The primary endpoint is the 5-year overall survival (OS). The secondary endpoints are 3-year OS, 5-year disease-free survival (DFS), short-term outcomes as well as quality of life. Discussion This is the first prospectively randomized controlled trial designed to compare RAE with MIE as surgical treatment for resectable ESCC. According to our hypothesis, RAE will result in at least similar oncologic outcomes and long-term quality of life, but with a shorter operation time, lower percentage of perioperative complications, lower blood loss, and shorter hospital stay when compared with MIE. This study started in July 2017. Follow-up will terminate after 5 years from the time when the last patient was enrolled. Trial registration ClinicalTrial.gov: NCT03094351 (March 29, 2017). The trial was prospectively registered.